2017
DOI: 10.1039/c7se00176b
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-less photoelectrochemical cells: product separation by hydrodynamic control

Abstract: A key step in order to realise photo-electrochemical (PEC) water splitting to produce hydrogen sustainably, is reactor design. Good engineering will minimise energy losses (both optical and ohmic) due to reactor construction, whilst ensuring the H 2 and O 2 produced are separated, and this can subsequently relax the requirements on the photo-absorber material and/or electrocatalysts. In this paper we show that separation of the products through hydrodynamic flow alone would negate the need for the conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 55 publications
1
33
0
2
Order By: Relevance
“…The electrolyte ow, light scattering and reection due to bubbles and other optical phenomena, pH and temperature changes were not included in the present model, which will be extended to include them, based on the studies of Singh, 15 Haussener 16 and Holmes-Gentle. 61…”
Section: Discussionmentioning
confidence: 99%
“…The electrolyte ow, light scattering and reection due to bubbles and other optical phenomena, pH and temperature changes were not included in the present model, which will be extended to include them, based on the studies of Singh, 15 Haussener 16 and Holmes-Gentle. 61…”
Section: Discussionmentioning
confidence: 99%
“…From this point of view, a lower bias-free photocurrent can even prove beneficial for commercial systems by preventing bubble formation. [127] In this case, the dissolved gas could be removed from the PEC cell and separated in a recirculating system, which can be powered by the additional driving force of up to 0.6 V of the tandems. To mitigate the effect of device degradation and resistive losses on the overall performance of such assemblies, a tiled design consisting of smaller wireless tandems could be constructed, where any faulty device could be simply replaced.…”
Section: Comparison With State-of-the-art and Outlookmentioning
confidence: 99%
“…Here, we use two-dimensional (2-D) nite element modeling to quantify the different scale-up related loss mechanisms in a solar-water splitting device: substrate ohmic loss, electrolyte ohmic loss, and local pH-gradient related losses. We consider a membrane-less water splitting device, where the product (i.e., O 2 and H 2 ) separation is done using hydrodynamic control, 29,30 operated with buffered electrolyte at neutral pH. Although the use of neutral pH increases the potential drop in the cell (i.e., due to the evolving pH-gradient and the associated overpotentials), a device operating at neutral pH allows the use of abundant seawater and is safer to operate over large collection areas.…”
Section: Introductionmentioning
confidence: 99%
“…In such a conguration, hydrodynamic ow alone is sufficient to separate the products and ensure safe operation without the use of conventional membranes. 29,30 Since it has been shown that the voltage losses associated with scale-up are not due to additional potential drop within the light absorbers, 21 only dark electrochemical reactions are taken into consideration here. For our analysis to be valid, the resistance of the semiconductor layer itself should therefore be negligible and the deposition at large area should still result in homogenous lms.…”
Section: Introductionmentioning
confidence: 99%